Rwanda: Recent developments in agricultural research - Flaherty, Kathleen; Munyengabe, Jean Marie (Rwanda Agricultural Research Institute, 2011)
The war and accompanying Tutsi genocide of the early 1990s devastated Rwanda's agricultural research agencies, and they continue to face challenges related to the resulting loss of human resource capacity and physical infrastructure. Nevertheless, since then the country has made progress in rebuilding its agricultural research and development (R&D) system. As of 2009, investment in agricultural R&D totaled 3.6 billion Rwandan francs or 19.2 million PPP dollars, both in 2005 constant prices, which represents a slight increase over 2005 levels, largely due to modest growth in the higher education sector after 2007 (Figure 1; Table 1). Unless otherwise stated, all dollar values in this note are expressed in purchasing power parity (PPP) prices.1